2014
DOI: 10.1039/c3fd00135k
|View full text |Cite
|
Sign up to set email alerts
|

Complex organic molecules along the accretion flow in isolated and externally irradiated protoplanetary disks

Abstract: The birth environment of the Sun will have influenced the physical and chemical structure of the pre-solar nebula, including the attainable chemical complexity reached in the disk, important for prebiotic chemistry. The formation and distribution of complex organic molecules (COMs) in a disk around a T Tauri star is investigated for two scenarios: (i) an isolated disk, and (ii) a disk irradiated externally by a nearby massive star. The chemistry is calculated along the accretion flow from the outer disk inward… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 118 publications
0
28
0
Order By: Relevance
“…Gasphase reactions are not efficient enough to explain many of the observed COM abundances, and it is generally accepted that such species form on the surfaces of icy dust grains by merging smaller species to larger and larger constituents. This idea, supported by numerous laboratory results and astrochemical simulations, indicates that surface reactions, triggered by accreting atoms, impacting cosmic rays and VUV photons, as well as by thermal processing, provide efficient pathways toward molecular complexity (Charnley & Rodgers 2008;Garrod et al 2008;Vasyunin & Herbst 2013b;Walsh et al 2014aWalsh et al , 2014bLinnartz et al 2015;Öberg 2016).…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Gasphase reactions are not efficient enough to explain many of the observed COM abundances, and it is generally accepted that such species form on the surfaces of icy dust grains by merging smaller species to larger and larger constituents. This idea, supported by numerous laboratory results and astrochemical simulations, indicates that surface reactions, triggered by accreting atoms, impacting cosmic rays and VUV photons, as well as by thermal processing, provide efficient pathways toward molecular complexity (Charnley & Rodgers 2008;Garrod et al 2008;Vasyunin & Herbst 2013b;Walsh et al 2014aWalsh et al , 2014bLinnartz et al 2015;Öberg 2016).…”
Section: Introductionmentioning
confidence: 69%
“…It rather complements these, showing that COMs of astrobiological importance can be formed as early as the cold dark cloud stage, during the CO freeze-out stage, and well before formation of the protostar and heating of the dust occurs. COMs produced on icy dust grains in this early stage of star formation can, in turn, be locked on the grain surface and participate in active energetic processing during later stages, or even be released into the gas phase by shocks, heat, or photodesorption (Charnley & Rodgers 2008;Caselli & Ceccarelli 2012;Walsh et al 2014aWalsh et al , 2014bJiménez-Serra et al 2016). Their efficient release into the gas phase by heat and photodesorption is unlikely, however, due to the low volatility of such complex species and a tendency of even the simplest COMs (e.g., CH 3 OH) to photodissociate and desorb as fragments, rather than as an intact molecule (Bertin et al 2016).…”
Section: Conclusion and Astronomical Relevancementioning
confidence: 99%
“…More recently, Walsh et al (2014a) modelled the abundances of complex organic molecules along multiple streamlines in a disc. The authors found that methanol was preserved along the midplane, prior to crossing of its snowline.…”
Section: Comparisons To Previous Workmentioning
confidence: 99%
“…However, even these gasgrain networks could not replicate the observed abundances of COMs, implying that key production pathways to COMs are still elusive. The crucial drawback of existing models is the assumption of an ice mantle of which only the first few monolayers participate in an active chemistry via diffusion-limited thermal surface reactions (11). This conjecture limits the validity of preceding gas-grain reaction networks because laboratory studies provided compelling evidence that an interaction of ionizing radiation in the form of cosmic rays and their secondary electrons with interstellar ices forms COMs as complex as sugars (12), amino acids (13), and dipeptides (14).…”
mentioning
confidence: 99%